Longitudinal analysis of financial performance of sawmills and wood construction element producers in Finland - Koskivaara, Atte; Lähtinen, Katja; Toppinen, Anne (Suomen metsätieteellinen seura, 2025)
The global outlook for wood construction is positive, driven by bio- and circular economy programs promoting wood use in construction. The industrialization of building processes is also seen as essential for improving construction efficiency and competitiveness. However, despite this positive outlook, wood construction in Finland remains a niche that has yet to reach its full potential. To reduce the dependency between the concrete and construction sectors, the wood element value chain needs competitive businesses to foster innovations and capture a larger market share in this highly competitive industry. However, the performance of two important stages of the value chain, sawmilling and wood element manufacturing, has not been measured in the scientific literature. The competitiveness of Finnish sawmills and wood element producers were analyzed by studying the industry’s financial performance using firm-level panel data and a regression approach over the 2012–2021 period. The results suggest higher variation across element producers’ profitability, while sawmills are more homogenous. Both value chain stages show signs of typical manufacturing industries, as materials and salaries proved to have a relatively high negative impact on competitiveness. However, differences were also found especially regarding short-term solvency and liquidity trends and average levels of costs and value-added. To understand competitiveness in the wood construction sector, an insight into intra- and inter-industry dynamics and value chain positioning is therefore required. Financially viable sawmilling and wood element firms are essential not only for business survival but for transforming the construction industry’s logic.
Keywords: business; competitiveness; financial analysis; innovation; profitability; value-added; wood construction